The Effect of Current Ratio (CR) and Debt to Asset Ratio (DAR) on Profit Growth at PT. Dharma Satya Nusantara Tbk - Izatul Yazidat; Aliah Pratiwi; Mukhlis (Pustaka Digital Indonesia, 2026)
This study examines the effects of the Current Ratio (CR) and Debt-to-Asset Ratio (DAR) on profit growth at PT Dharma Satya Nusantara Tbk during the 2013–2023 period. Profit growth is a key indicator of corporate financial performance, reflecting a firm's ability to sustain profitability and create long-term value. This research employs a quantitative associative approach using secondary data obtained from the company's audited annual financial statements. The study analyzes 11 years of financial data selected through a saturated sampling technique. Multiple linear regression analysis was performed using SPSS version 26, preceded by classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests, to ensure model validity. The empirical findings reveal that the Current Ratio does not have a statistically significant effect on profit growth, indicating that higher liquidity does not necessarily translate into increased profitability. Conversely, the Debt-to-Asset Ratio has a positive and significant effect on profit growth, suggesting that an optimal capital structure supported by debt financing contributes to improved corporate earnings. Simultaneously, the Current Ratio and Debt-to-Asset Ratio significantly influence profit growth, demonstrating that liquidity and leverage jointly explain variations in corporate financial performance. The model explains 60% of the variation in profit growth, while the remaining 40% is attributable to other factors not included in this study. These findings provide practical insights for corporate managers and investors in evaluating financial performance and developing effective financing strategies to support sustainable profit growth.